How acoustic refurbishment of a classroom affected pupils and sound levels - A natural experiment - Hongisto Valtteri; Lindberg Mikko; Lahti Aleksi; Veermans Marjaana; Alakoivu Reijo; Radun Jenni (Italia, 2025)
We determined how pupils perceive activity noise in classrooms A and B having different room acoustic qualities. Classroom A was traditional (reverberation time 0.54 s). Additional noise control was applied in classroom B (0.32 s). In both classrooms, teachers kept controlled lessons according to four activity types. During the controlled lessons, activity sound levels were measured. At the end of each controlled lesson, pupils' experiences were inquired using a questionnaire. In general, the most annoying sound source was other pupils' speech. More pupils were annoyed by it in classroom A (65%) than in classroom B (15%). Activity sound levels during controlled lessons were 2-13 dB lower in classroom B. Noise control might reduce pupils' noise annoyance and enable quieter activity especially during the loudest lesson types.
Proceedings of Forum Acusticum 2023 : 10th Convention of EAA